From BIM to computational BIM: A systematic review of visual programming application in building research - Taki Eddine Seghier; Chavanont Khosakitchalert; Ziwen Liu; Chukwuka Christian Ohueri; Yaik-Wah Lim; Ahmad Fahmi Bin Zainazlan (Ain Shams Engineering Journal)
The architecture, engineering, construction, and operation (AECO) industry has embraced the combination of building information modelling (BIM) and computational algorithms to advance digital transformations. Computational BIM has enabled the development and testing of various BIM-based solutions for the building industry. This study conducted a systematic review of the application of computational BIM through visual programming (VP) in building research. The study employed a hybrid approach of bibliometrics and content analyses using seventy-nine publications filtered from Scopus and Web of Science databases. The bibliometric analysis identified publication frequency trends, journal distributions, country distributions, eminent authors, co-authorship networks, and keyword co-occurrence networks. The content analysis identified six key research themes and four major methodological roles of computational BIM in building research. A research framework is proposed to summarize and articulate the state of the art of computational BIM application in building research, research gaps, and future research directions.